Social Media-Based Marketing Management in Increasing the Number of New Students - Uswatun Hasanah (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STITNU Al-Farabi Pangandaran, 2026)
The number of new student enrollments at MTs YPP Babakan Jamanis Parigi remains relatively low despite the school's use of social media as a promotional platform. This condition indicates that the implementation of social media-based marketing management has not been optimized to enhance the school's attractiveness amid increasing competition among educational institutions. This study aims to analyze the implementation of social media-based marketing management in increasing new student enrollment and to identify the supporting and inhibiting factors affecting its implementation. This research employed a descriptive qualitative approach. The research participants consisted of the principal, the New Student Admission (PPDB) committee, and the student council (OSIS) administrators at MTs YPP Babakan Jamanis Parigi. Data were collected through observation, interviews, and documentation, and were analyzed using qualitative data analysis techniques. The findings reveal that social media has been utilized as a school marketing strategy; however, its implementation has not been consistent, particularly in terms of posting frequency and the development of engaging content. Supporting factors include the principal’s commitment and collaboration with a local football club and a woodworking company. Meanwhile, the inhibiting factors include inconsistent content posting, limited attractiveness of promotional content, and intense competition with other schools. Therefore, MTs YPP Babakan Jamanis Parigi should develop a more systematic digital marketing strategy by establishing a regular posting schedule, creating creative and relevant content, and optimizing the use of social media as a promotional tool to increase new student enrollment.